Regulation of asthmatic airway relaxation by estrogen and heat shock protein 90 - S. Intapad (2018)
We tested the hypothesis that asthmatic mouse airways exhibit impaired relaxation to NO donors. Mouse tracheal rings were incubated overnight in serum from asthmatic human subjects or from nonasthmatic controls. The next day, cumulative concentration-response curves (CCRC) to sodium nitroprusside (SNP) and nitroglycerine (NTG) were obtained. Both SNP and NTG relaxed the pre-constricted normal tracheal rings. Tracheal rings exposed to serum from asthmatic patients exhibited a more than a threefold increase in the EC50 of SNP and NTG. Pre-incubation of tracheal rings with heat shock protein 90 inhibitors decreased the relaxation of both normal and asthmatic tracheal rings to SNP and NTG. Pre-incubation with estradiol did not affect normal tracheal ring relaxation but exhibited an increase in asthmatic tracheal ring relaxation, which was abolished by an estrogen receptor (ER) antagonist. ER subtype-selective agonists, but not GPR30 agonists, mimicked the action of estradiol on tracheal ring relaxation. Co-incubation of rings with radicicol and estradiol produced an ER-dependent increase in the relaxation response to SNP of both normal and asthmatic ASM. Estrogen-induced relaxation of ASM was abolished by overnight incubation with radicicol and this was associated with reduced expression of ERβ. These data suggest that asthmatic ASM is considerably less responsive to NO-donors and that both estrogen and hsp90 play important roles in ASM relaxation. © 2011 Wiley Periodicals, Inc.